Microbial synergy between Azospirillum brasilense and Glomus iranicum promotes root biomass and grain yield in Andean quinoa cultivars - Gutierrez, Miriam (2026)
Quinoa (Chenopodium quinoa Willd.) is a strategic crop for climate-smart agriculture in the Andes, yet yield gains are constrained by soil degradation and low-input systems. We tested whether synergistic bioinoculation with a plant growth-promoting rhizobacterium (Azospirillum brasilense) and an arbuscular mycorrhizal fungus (Glomus iranicum var. tenuihypharum) enhances root function and grain productivity under field conditions. A split-plot RCBD was conducted in Ayacucho, Peru (2735 m a.s.l.) using four cultivars, Blanca de Junín (BJ), INIA 441 Señor del Huerto (SH), INIA 415 Pasankalla (RP) and INIA 420 Negra Collana (NC) and four treatments: uninoculated control, Azospirillum, Glomus and co-inoculation. Vegetative, root and yield traits were quantified; ANOVA, Tukey/Dunnett contrasts, correlations and PCA were applied. Co-inoculation consistently outperformed single inoculants, increasing root diameter, length, branching, dry weight and volume dry weight, while also enlarging panicle dimensions and raising grain weight per panicle and thousand-seed weight. Grain yield reached 4.94 ± 0.59 t ha⁻¹ under co-inoculation, almost triple that of the control (1.71 ± 0.28 t ha⁻¹) and about 1.5 times higher than single inoculations. Genotypic effects were pronounced; BJ and SH combined superior root biomass with higher yield, RP maximized grain size and hectoliter weight, whereas NC responded weakly. Significant genotype × treatment interactions indicated cultivar-dependent microbiome benefits. Correlation and PCA linked root biomass and stem/panicle architecture to yield formation, positioning co-inoculation along trait vectors associated with belowground vigor and productivity. These results demonstrate a robust microbial synergy that translates root gains into yield, supporting co-inoculation as a scalable, low-input strategy for sustainable intensification of quinoa in highland agroecosystems.